Incentivizing Change Within Social Determinants of Health Using Blockchain Technology - McFarlane, Chrissa; Finch, Marquesa; Gray, Tiffany R.; Fuchs, Jonathan M.; Hersh, William; Clouse, John (Frontiers in Blockchain, 2020)
There are growing initiatives and calls to focus greater attention to the social determinants of health (SDOH) and their impact on population health (Heiman and Artiga, 2015). Several emerging strategies are being used to begin to address social determinants, such as the use of health impact assessments and applying health in all policies (HiAP). These strategies and tools are being implemented in an effort to review existing and needed policies, as well as to propose new policies to lessen health disparities (Koh et al., 2011). Efforts to further integrate SDOH through the use of health information technology and other emerging technologies, such as distributed ledger technology both in and outside of existing healthcare systems, are also increasing (Koh et al., 2011). Understanding and addressing the SDOH through both traditional and non-traditional sectors is key to further reducing health disparities (Heiman and Artiga, 2015; Cottrell et al., 2018; McGinnis et al., 2002). Through exploration of the current state of SDOH in the healthcare industry, an analysis of blockchain technology will render the acceleration and adoption of SDOH to effectively provide improved health outcomes.